RESPON PERKECAMBAHAN BENIH DAN PERTUMBUHAN SEMAI PINUS (PINUS MERKUSII JUNG ET DE VRIESE) DENGAN APLIKASI KONSENTRASI DAN LAMA PERENDAMAN LARUTAN ABITONIK - Chanan, M. (Jurnal Gamma, 2009)
The research aims to study the response of seed germination and seedling growth of pine(Pinus merkusii jung et de vriese) with the application of solution concentration and dipping timeabitonik conducted in South Pujon seedbed RPH, BPKH Pujon, KPH Malang. The experimentbegan in September 2008 until May 2009.The research method used was a factorial experiment with Randomized Block Design (RBD),consisting of two factors, namely the first factor and second factor soaking Abitonik growth regulatorconcentration. Factor I: Long soaking, consists of three levels: P1 = Old soaking 20 minutes, P2 =Length of 40 minutes of immersion, submersion Old P3 = 60 minutes or 1 hour, Factor II:Concentration of growth regulators Abitonik, K1 = Concentration of solution 0, 04 cc / liter ofwater., K2 = concentration of solution 0.06 cc / liter of water., K3 = concentration of solution 0.08cc / liter of water, K4 = Concentration of solution 0.1 cc / liter of water.The research data from each observation parameters were analyzed by variance in accordancewith the randomized block design (RBD), the analysis was tested by using F test with a level of 5%.To compare among the treatments with one another treatment used Duncan?s test at 5% level.There is interaction between soaking time and concentration of growth regulators on theparameter Abitonik high seedling age 26 and 31 days after planting, total seedling leaf age 21 daysafter planting, and germination value. While the concentration of growth regulators Abitonik notprovide significant effect on germination of seeds Phinus. Parameters perlakuanlama germinationpercentage at 60 minutes of immersion (P3) of 59.73% and the concentration of 0.1 cc / l water (K4)of 59.22%.